2013
DOI: 10.1093/jscr/rjt035
|View full text |Cite
|
Sign up to set email alerts
|

Cortical blindness as a rare presentation of cerebral venous thrombosis

Abstract: Cerebral venous thrombosis (CVT) remains a diagnostic and therapeutic challenge for clinicians. Manifesting in a remarkably wide spectrum of symptoms and signs, CVT often presents in a misleading fashion—if unrecognized or misdiagnosed, it carries potentially fatal consequences. Visual loss is quite rare as the initial presentation of CVT and is typically a finding more frequent in chronic cases with associated papilledema on funduscopy Ferro, Lopes, Rosas and Fontes (Delay in Hospital Admission of Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This loss of vision is often reversible, to some extent, and while patients may have residual visual field defects, sometimes vision is fully restored. Wang et al ( 2013 ) reported a case of an 18-year-old female who had a history of headache for 3 weeks and developed acute bilateral blindness after a nap. Both pupils and an ophthalmoscopy were normal, and both eyes showed no light perception.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…This loss of vision is often reversible, to some extent, and while patients may have residual visual field defects, sometimes vision is fully restored. Wang et al ( 2013 ) reported a case of an 18-year-old female who had a history of headache for 3 weeks and developed acute bilateral blindness after a nap. Both pupils and an ophthalmoscopy were normal, and both eyes showed no light perception.…”
Section: Clinical Featuresmentioning
confidence: 99%